(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This community service program aimed to empower a group of crushed-stone artisans in Buluri Subdistrict, Palu City, who have long depended on sand and stone quarrying (Category C mining) with low- and unstable-income levels. In this area, stone dust waste is abundantly available but has not been optimally utilized, despite its potential as an additive material in paving block production. The program was designed to enhance the technical and managerial capacities of the partner group through a series of training activities covering material mixing, manual molding, curing techniques, product quality standardization, digital marketing strategies, and basic business simulation. Program evaluation was conducted through observations of participant engagement, assessment of paving block quality, and monitoring of the implementation of simple financial records and digital marketing practices. The results show that the partner group was able to produce stone-dust-based paving blocks with a capacity of approximately 100 units per day, featuring more uniform quality and approaching the minimum quality standard of K-200. From a managerial perspective, the group began to apply simple financial bookkeeping and to formulate a collective business plan. In terms of marketing, the partners utilized social media platforms such as WhatsApp Business and Instagram for product promotion and initiated communication with local building material stores. Overall, this community service activity successfully improved technical skills, strengthened institutional capacity, created opportunities for sustainable community-based enterprises, and generated environmental benefits through the utilization of stone dust waste as a value-added construction material. Keywords: Community empowerment, stone dust, paving blocks, local economy, digital marketing. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberdayakan kelompok pengrajin batu pecah di Kelurahan Buluri, Kota Palu, yang selama ini bergantung pada aktivitas tambang Galian C dengan tingkat pendapatan yang rendah dan tidak stabil. Di wilayah ini, limbah abu batu tersedia dalam jumlah melimpah namun belum dimanfaatkan secara optimal, padahal memiliki potensi sebagai bahan tambahan dalam pembuatan paving blok. Program pengabdian dirancang untuk meningkatkan kapasitas teknis dan manajerial mitra melalui serangkaian pelatihan yang meliputi pencampuran material, pencetakan manual, teknik curing, standarisasi mutu produk, pemasaran digital, serta simulasi usaha berbasis kelompok. Evaluasi kegiatan dilakukan melalui observasi partisipasi peserta, penilaian kualitas produk paving blok, serta pemantauan penerapan pencatatan usaha dan strategi pemasaran digital. Hasil kegiatan menunjukkan bahwa mitra mampu memproduksi paving blok berbasis abu batu dengan kapasitas sekitar 100 unit per hari dengan kualitas yang lebih seragam dan mendekati standar mutu minimal K-200. Dari sisi manajerial, kelompok mitra mulai menerapkan pencatatan keuangan sederhana dan menyusun rencana usaha bersama. Pada aspek pemasaran, mitra telah memanfaatkan media sosial seperti WhatsApp Business dan Instagram untuk promosi produk serta menjalin komunikasi awal dengan toko bangunan setempat. Secara keseluruhan, kegiatan pengabdian ini berhasil meningkatkan keterampilan teknis, memperkuat kapasitas kelembagaan, membuka peluang usaha berkelanjutan, serta memberikan manfaat lingkungan melalui pemanfaatan limbah abu batu sebagai produk konstruksi bernilai ekonomi. Kata Kunci: Pemberdayaan masyarakat, abu batu, paving blok, ekonomi lokal, pemasaran digital